2017
DOI: 10.1016/j.carbon.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbon nanotube defects on fracture mechanisms in ceramic nanocomposites

Abstract: Carbon nanotubes (CNTs) can improve the fracture toughness of ceramic composites. It is widely believed that defects in the CNTs will alter key properties that ultimately dictate composite toughening. However, to date there have been no studies that directly correlate these specific properties to controlled defect levels in CNTs. This type of investigation is presented here, using ceramic nanocomposites with a polymer derived ceramic (PDC) matrix, reinforced with multiwalled CNTs. This work includes basic frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Where Fmax is the maximum measuring force applied to the CNT and l emb is the length of the CNT embedded in the matrix. This formula can provide an effective strategy for improving nanocarbon-reinforced ceramic matrix composites [82]. But in boron nitride sheet, it will result in a sharp decrease in mechanical performance when defect percentage is greater than 1% [83].…”
Section: Non-chemical Combinationmentioning
confidence: 99%
“…Where Fmax is the maximum measuring force applied to the CNT and l emb is the length of the CNT embedded in the matrix. This formula can provide an effective strategy for improving nanocarbon-reinforced ceramic matrix composites [82]. But in boron nitride sheet, it will result in a sharp decrease in mechanical performance when defect percentage is greater than 1% [83].…”
Section: Non-chemical Combinationmentioning
confidence: 99%
“…Most recently, Lou et al [182,183] have designed and developed a micro-fabricated device shown in Figure 15(a), which can perform the tensile testing and pullout experiment [184][185][186][187][188][189]. The microdevice uses a spring-like 'push-pull' mechanism, consisting of three moveable shuttles attached to each other via inclined freestanding beams.…”
Section: Micromechanical Devices With Push-pull Mechanismmentioning
confidence: 99%
“…On the other hand, bonding at the CNT/polymer interface (covalent, van der Waals) also plays a decisive role to enhance the uniformity of the CNT dispersion into the polymer matrix [ 136 ]. Therefore, to obtain the desired properties of CNT/polymer composites, such as the thermal, mechanical and electrical properties [ 8 , 10 , 137 ], the characterization of surface properties including the CNT surface orientation and surface defects are also important [ 138 140 ]. The defects can have both positive (increasing the bonding at the interface and between carbon structures [ 25 , 137 , 139 , 141 ]) and negative (reduction of the quality of physical properties [ 10 , 141 ]) effects on the application and quality of composites.…”
Section: Reviewmentioning
confidence: 99%